(untitled) (Research, Society and Development, 2024)
This study presents a case report of a female patient, a premature newborn, diagnosed with extensive and obstructive stenosis of the bilateral ureteropelvic junction (UPJ) who developed renal failure after birth, a rare congenital condition in neonates. The patient, weighing 2,235 g, underwent a surgical procedure of Anderson-hynes dismembered pyeloplasty at 15 days of age, ewith favorable clinical evolution and significant improvement in renal function. The main objective of this study is to enrich the medical literature with pertinent information about this congenital anomaly and demonstrate the feasibility of performing this surgical procedure in newborns, including those with low birth weight. This case highlights the importance of early diagnosis and timely surgical intervention to increase survival and improve the quality of care provided to patients with UPJ stenosis. Furthermore, the study aims to stimulate future research and the development of diagnostic reasoning, as well as sensitize the healthcare team to the early detection of this rare condition.